Telehealth for the Initial Evaluation of Musculoskeletal Disorders: Qualitative Study of Patients, Health Care Providers, and Key Stakeholders in the Province of Quebec in Canada - Raphaël Vincent; Pauline Lemersre; Geneviève Ferland; Annie Bélanger; Audrey-Anne Cormier; Kadija Perreault; Jean Sébastien Roy; Nicolas Pinsault; Dahlia Kairy; François Desmeules (Journal of Medical Internet Research, 2025)
Abstract BackgroundAccess to care for patients with musculoskeletal disorders (MSKDs) remains a significant challenge. Telehealth has emerged as a promising solution to improve access to care. However, conducting initial evaluations of MSKDs remotely raises concerns about patient safety and clinical efficacy due to the necessary adaptations required for a clinical examination and the challenges of obtaining an accurate and reliable diagnosis. ObjectiveWe aim to explore the use of telehealth for the initial evaluation of MSKDs in the province of Quebec, Canada. Through semistructured interviews with selected patients, health care providers, and other key stakeholders involved in telehealth, this study aims to provide a comprehensive and detailed understanding of its application, benefits, and challenges. MethodsSemistructured interviews were conducted in the province of Quebec with patients, clinicians, telehealth software specialists, and professional bodies’ representatives. Five tailored interview guides were developed using the Consolidated Framework of Implementation Research and the Framework of Mathieu-Fritz and Esterle for the study of telehealth interventions. The themes explored included participants’ prior experiences with telehealth, perceived strengths and limitations of telehealth, particularly regarding the initial evaluation and diagnosis of new patients, and the current global environment of telehealth use. All interviews were transcribed verbatim, and a reflexive thematic analysis was performed using the Mathieu-Fritz Framework. ResultsThirty-eight participants, including patients (n=11), health care providers (family physicians and musculoskeletal medical specialists: n=11; and physiotherapy professionals: n=10), telehealth software specialists (n=2), and representatives from professional bodies (n=4), shared their perspectives on telehealth for the initial evaluation of MSKDs. Five key themes emerged: (1) several participants viewed telehealth, including remote evaluations, as a solution to improve access to care; (2) patients and health care providers reported that a remote evaluation was more appropriate for simpler MSKD presentations; (3) some health care providers expressed concerns about the potential for an increase in diagnostic errors and the challenges of performing all usual components of a standard MSKD physical examination remotely; (4) patients expressed doubts about their ability to effectively perform certain tasks or tests on themselves; and (5) broader challenges were also highlighted by all participants, such as the impact on the patient-clinician relationship, access to appropriate hardware, digital literacy, and confidentiality concerns. ConclusionsTelehealth is seen as a valuable solution to improve access to care for patients with MSKDs, especially for simpler cases or urgent needs. However, remote physical examination poses challenges associated with concerns about diagnostic accuracy and limited remote physical examination procedures and components. Effective implementation will likely require more evidence-based guidelines, provider training on remote techniques and strategies to maintain patient-provider relationships. Addressing access to technology, digital literacy, and privacy concerns is also essential to ensure equitable adoption and to optimize telehealth in musculoskeletal care.